Transient expression of neuropeptide W in postnatal mouse hypothalamus – A putative regulator of energy homeostasis. (20th August 2015) - Motoike, T.; Skach, A.G.; Godwin, J.K.; Sinton, C.M.; Yamazaki, M.; Abe, M.; Natsume, R.; Sakimura, K.; Yanagisawa, M.
Highlights: We investigate the expression of neuropeptide W (NPW) in postnatal mouse brain. NPW is co-expressed in NPY neurons in postnatal hypothalamus. We generated NPW-iCre knock-in mouse line. Adult neurons, matured from NPW-positive postnatal neurons, are sensitive to leptin. Abstract: Neuropeptide B and W (NPB and NPW) are cognate peptide ligands for NPBWR1 (GPR7), a G protein-coupled receptor. In rodents, they have been implicated in the regulation of energy homeostasis, neuroendocrine/autonomic responses, and social interactions. Although localization of these peptides and their receptors in adult rodent brain has been well documented, their expression in mouse brain during development is unknown. Here we demonstrate the transient expression of NPW mRNA in the dorsomedial hypothalamus (DMH) of postnatal mouse brain and its co-localization with neuropeptide Y (NPY) mRNA. Neurons expressing both NPW and NPY mRNAs begin to emerge in the DMH at about postnatal day 0 (P-0) through P-3. Their expression is highest around P-14, declines after P-21, and by P-28 only a faint expression of NPW and NPY mRNA remains. In P-18 brains, we detected NPW neurons in the region spanning the subincertal nucleus (SubI), the lateral hypothalamic (LH) perifornical (PF) areas, and the DMH, where the highest expression of NPW mRNA was observed. The majority of these postnatal hypothalamic NPW neurons co-express NPY mRNA. A cross of NPW-iCre knock-in mice with a Cre-dependent tdTomato reporter line revealed that more than half of the reporter-positive neurons in the adult DMH, which mature from the transiently NPW-expressing neurons, are sensitive to peripherally administrated leptin. These data suggest that the DMH neurons that transiently co-express NPW and NPY in the peri-weaning period might play a role in regulating energy homeostasis during postnatal development.